1996
DOI: 10.1002/(sici)1097-4695(199601)29:1<115::aid-neu9>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Post-translational regulation of neuronal acetylcholine receptors stably expressed in a mouse fibroblast cell line

Abstract: Second messenger regulation of neuronal acetylcholine receptors (AChRs) was investigated in a mouse fibroblast cell line, M10, stably transfected with chicken α4 and β2 cDNAs. Both forskolin and 8‐bromo‐cyclic adenosine 3′,5′‐monophosphate (cAMP) induced large increases in the numbers of AChRs. The increases were due in part to increased transcription and translation of the α4 and β2 genes. Blockade of protein synthesis with cycloheximide, however, revealed that forskolin also exerts a post‐translational effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 37 publications
1
23
0
Order By: Relevance
“…It has been suggested that this "persistent inactivation" may be a consequence of the receptor adopting a long-lasting desensitized state. A 2-fold up-regulation in the level of cell-surface ␣4␤2 nAChR has also been reported as a consequence of treatments which elevate intracellular cAMP (26). It has also been shown previously that subunit folding and assembly of some nAChRs, notably those of invertebrates and of cold water fish such as Torpedo, when expressed in mammalian cell lines, is more efficient at lower temperatures (27,28).…”
mentioning
confidence: 70%
“…It has been suggested that this "persistent inactivation" may be a consequence of the receptor adopting a long-lasting desensitized state. A 2-fold up-regulation in the level of cell-surface ␣4␤2 nAChR has also been reported as a consequence of treatments which elevate intracellular cAMP (26). It has also been shown previously that subunit folding and assembly of some nAChRs, notably those of invertebrates and of cold water fish such as Torpedo, when expressed in mammalian cell lines, is more efficient at lower temperatures (27,28).…”
mentioning
confidence: 70%
“…The efficiency of subunit assembly can be regulated under certain conditions leading to higher nAChR expression. Studies in mouse fibroblasts showed that increased intracellular cAMP levels increase nAChR assembly efficiency and surface expression [19,20]. Another mechanism emerging as an important modulator of nAChR expression involves association with chaperone proteins that transport receptors away from the endoplasmic reticulum [8].…”
Section: Discussionmentioning
confidence: 99%
“…These intracellular nAChRs may consist of two distinct pools: nAChRs destined for immediate surface expression and nAChRs stored as an independent pool. Intracellular nAChR pools in other tissues (Stollberg and Berg, 1987) and recombinant cell lines (Whiteaker et al, 1998) can be modulated (Rothhut et al, 1996) and may be involved with the receptor turnover process. It is also possible that these intracellular nAChRs may represent internalized receptors that were once on the receptor surface.…”
Section: Discussionmentioning
confidence: 99%
“…These include alterations in nAChR formation and assembly (Mitra et al, 2001), nAChR transport to the cell surface (Rothhut et al, 1996;Keller et al, 2001), or nAChR stabilization in the cellular membrane (Peng et al, 1994). The rate-limiting processes involved in nAChR turnover remain to be determined and may vary with different disease conditions.…”
mentioning
confidence: 99%